(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Data on body measurements like BL (body length), CG (chest girth), WH (wither height) TM (test day milk production), PM (peak milk production), LP (lactation period), CFDC (cost for concentrate feed before test day milk production per cow), GGU (green grass used before test day milk production per cow) and husbandry practices, were collected from a total of 100 dairy cattle at the villages of Islampur upazila under the district of Jamalpur in Bangladesh from January to February 2017. Collected data were analyzed using SPSS software. The highest BL, CG, WH, CFDC and GGU were 175.71±0.42 cm, 161.74±0.24 cm,123.82±0.11 cm 125.54±0.24 bdt/cow/day and 27.29±0.89 kg/cow/day, respectively. The highest amounts of TM, PM and LP were 9.36±0.60 liter/cow, 13.11±0.54 liter/cow and 247.14±1.47 days/cow, respectively. BL, CG and WH increased with increased of the age of crossbred cattle up to 150 months of old. Similarly, CFDC and GGU increased with the increased of the age of crossbred cattle up to 150 months of old. Farmers in the study area were not interested to keep breeding bulls for breeding purpose but they were using artificial insemination system to inseminate their cows and aware about production performance record of the inseminating bull. Farmers took health services from milk vita and sold milk to the same. They believed that dairy cattle rearing a profitable livelihood. TM, PM and LP increased with the increased of the age of crossbred cattle up to 150 months of old. However, increase of CFDC will increase TM, LP and PM but increase of GGU will increase only LP. On the other hand increase of CG will increase TM and increase of BL will increase LP and PM. Res. Agric., Livest. Fish.4(2): 91-98, August 2017